2015
DOI: 10.5758/vsi.2015.31.3.87
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Features and Early Outcomes of Endovascular Repair of Abdominal Aortic Aneurysm from a Korean Multicenter Registry

Abstract: Purpose:To introduce a nation-based endovascular aneurysm repair (EVAR) registry in South Korea and to analyze the anatomical features and early clinical outcomes of abdominal aortic aneurysms (AAA) in patients who underwent EVAR.Materials and methods:The Korean EVAR registry (KER) was a template-based online registry developed and established in 2009. The KER recruited 389 patients who underwent EVAR from 13 medical centers in South Korea from January 2010 to June 2010. We retrospectively reviewed the anatomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
3
0
6
Order By: Relevance
“…Few studies have reported the suitability for EVAR among Korean patients. One study from a Korean multicenter registry reported that the mean suprarenal and infrarenal angulations were 33.9° and 46.8°, respectively, and the mean aortic neck length was 35.0 mm [ 9 ]; however, this study only included patients undergoing EVAR. Another study demonstrated that the suitability of aortic neck anatomy in Korean patients was 63%, the mean length was 28.0 mm, and the mean infrarenal angulation was 47.5° in 192 patients [ 10 ]; however, this study included AAAs more than 4 cm in maximal diameter, so did not represent typical patients requiring treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported the suitability for EVAR among Korean patients. One study from a Korean multicenter registry reported that the mean suprarenal and infrarenal angulations were 33.9° and 46.8°, respectively, and the mean aortic neck length was 35.0 mm [ 9 ]; however, this study only included patients undergoing EVAR. Another study demonstrated that the suitability of aortic neck anatomy in Korean patients was 63%, the mean length was 28.0 mm, and the mean infrarenal angulation was 47.5° in 192 patients [ 10 ]; however, this study included AAAs more than 4 cm in maximal diameter, so did not represent typical patients requiring treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as ethnicity and sex, are known to be associated with suitability for EVAR, with a lower percentage among Asians and women [ 7 , 8 ]. Although there have been a few reports regarding the aortoiliac anatomy of AAAs in Asian patients, the results have been inconsistent because of the small number of patients and the different inclusion criteria for analysis [ 7 , 9 - 11 ]. Therefore, further work is necessary to investigate the aortoiliac anatomy in Asians, and determine whether there are significant differences between different Asian populations, as well as between Asian and Western patients.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease was defined as a history of myocardial infarction or angina, percutaneous coronary intervention, coronary artery bypass grafting, and/or ischemic ST segment abnormalities on preoperative electrocardiography [13]. Patient with a serum creatinine level > 1.7 mg/dL were considered to have decreased renal function [14]. …”
Section: Methodsmentioning
confidence: 99%
“…Em 1991 a primeira endoprótese bifurcada foi implantada com sucesso e o FDA -Food and Drug Administration -aprovou as duas primeiras endopróteses para uso disseminado. Desde então, tem havido avanços progressivos no design desses dispositivos, permitindo o tratamento de casos cada vez mais complexos anatomicamente 49,53,55,56 .…”
Section: O Período Moderno Da Cirurgia De Aneurismas Começou Em 1817 ...unclassified
“…Em torno de 17% a 40% dos doentes com AAA apresentam aneurisma de artéria ilíaca 55,69,[95][96][97] . Dentre os aneurismas de ilíaca, 70% ocorrem na ilíaca comum, 20% na interna e 10% na externa e até um terço dos AAI são bilaterais.…”
Section: Diâmetro Aorto -Ilíaco E Anatomiaunclassified